Current Legal Policies for Female Employees and Some Recommendations - Phan Thị Thanh Huyền (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Female workers are not only a large proportion of the labor force, but increasingly show their roles, abilities and creativity in all areas of social life, adapting to the integration and development of the world economy. Like other countries, in Vietnam today, the political trend towards human rights and the advancement of women is considered as a factor promoting the progress of half of the society. However, there is still a big gap between the goal and reality. It is the specific social characteristics and existing shortcomings of legal policies that hinder female workers in the process of liberating themselves, affirming their capacity and qualities, and reduce their ability to contribute to society. Therefore, in addition to further promoting the struggle for the advancement of women, gender equality, removing all political, economic and ideological barriers for female workers to integrate into society, it is extremely important to strengthen the completion and dissemination of legal policies for female workers so that they can realistically and fully receive their rights.